Using E-GARCH to Analyze the Impact of Investor Sentiment on Stock Returns Near Stock Market Crashes - Chen, Sze Ting; Haga, Kai Yin Allison (Frontiers in Psychology, 2021)
Purpose: Investor sentiment, the willingness of market participants to invest, is a difficult concept to measure. Exploring the relationship between investor sentiment and stock returns can reveal how investor sentiment affects the operation of the stock market. Such an understanding can assist market participants to make more rational investment decisions based on market laws. Methodology: Although the E-GARCH model has the advantage of considering volatility clustering, it has not previously been used to investigate the impact of investor sentiment changes on the Shanghai Composite Index's market return. This research therefore applies the E-GARCH approach to data from 2013 to 2016, to explore the influence of investor sentiment on the return rate of the Shanghai Composite Index. Main Findings: There is a positive relationship between the market yield and changes in investor sentiment: when investor sentiment is optimistic the market yield tends to increase. However, the asymmetric effect coefficient in the E-GARCH model is significantly less than 0, with negative shocks having more impact on the market return than positive shocks. This indicates that there is a leverage effect in the market over the entire period from 2013 to 2016. Results: The meaning of a negative asymmetric effect coefficient is that, in comparing an increase in investor sentiment versus an equally-sized decrease, the sentiment increase had less effect on the market rate of return before a stock market crash than the decrease had after a crash. Application: Based on these research results, this article can provide insights to understand how investors’ subjective judgments on future earnings affect their investment behavior and have a great impact on the market. It also can help investors make more rational investment decisions based on an understanding of market laws, and help regulators with guidance for their supervision and policy making. Originality/Value: This paper contributes to the theory of investor sentiment index, improving the index construction method by adding two sentiment proxy indicators, investor activity ACT and stock market leverage level. After constructing the sentiment index and comparing it with the stock market index (Shanghai Composite Index), the fit is found to improve.